Inhibition of AIM2 inflammasome activation by a novel transcript isoform of IFI16 - Wang, Pei‐Hui; Ye, Zi‐Wei; Deng, Jian‐Jun; Siu, Kam‐Leung; Gao, Wei‐Wei; Chaudhary, Vidyanath; Cheng, Yun; Fung, Sin‐Yee; Yuen, Kit‐San; Ho, Ting‐Hin; Chan, Ching‐Ping; Zhang, Yan; et al. (EMBO reports, 2018)
Mouse p202 is a disease locus for lupus and a dominant‐negative inhibitor of AIM2 inflammasome activation. A human homolog of p202 has not been identified so far. Here, we report a novel transcript isoform of human IFI16‐designated IFI16‐β, which has a domain architecture similar to that of mouse p202. Like p202, IFI16‐β contains two HIN domains, but lacks the pyrin domain. IFI16‐β is ubiquitously expressed in various human tissues and cells. Its mRNA levels are also elevated in leukocytes of patients with lupus, virus‐infected cells, and cells treated with interferon‐β or phorbol ester. IFI16‐β co‐localizes with AIM2 in the cytoplasm, whereas IFI16‐α is predominantly found in the nucleus. IFI16‐β interacts with AIM2 to impede the formation of a functional AIM2‐ASC complex. In addition, IFI16‐β sequesters cytoplasmic dsDNA and renders it unavailable for AIM2 sensing. Enforced expression of IFI16‐β inhibits the activation of AIM2 inflammasome, whereas knockdown of IFI16‐β augments interleukin‐1β secretion triggered by dsDNA but not dsRNA. Thus, cytoplasm‐localized IFI16‐β is functionally equivalent to mouse p202 that exerts an inhibitory effect on AIM2 inflammasome. Synopsis IFI16‐β, a novel transcript isoform of IFI16 is a functional homolog of mouse p202 and inhibits the AIM2 inflammasome. IFI16‐β impedes AIM2‐ASC complex formation and blocks cytoplasmic dsDNA sensing of AIM2. IFI16‐β shows a similar domain architecture than mouse p202. IFI16‐β associates with STING and is a weak inducer of type I interferons. IFI16‐β inhibits AIM2 inflammasome activation, and blocks its binding to cytoplasmic dsDNA. Graphical Abstract IFI16‐β, a novel transcript isoform of IFI16 is a functional homolog of mouse p202 and inhibits the AIM2 inflammasome. IFI16‐β impedes AIM2‐ASC complex formation and blocks cytoplasmic dsDNA sensing of AIM2.